2015
DOI: 10.1037/bne0000075
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol gains access to appetitive learning through adolescent heavy drinking.

Abstract: Adolescent heavy alcohol drinking increases the risk for alcohol use disorders in adulthood, yet mechanisms conferring increased risk are not well understood. We propose that adolescent alcohol drinking shapes alcohol’s aversive or appetitive properties in adulthood. Alcohol normally drives aversive learning and alcohol-predictive cues are avoided. We hypothesize that through adolescent heavy drinking alcohol gains access to appetitive learning. A primary consequence is that alcohol-predictive cues become valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
5
5
0
Order By: Relevance
“…Consistent with previous findings from our lab [ 5 , 7 ], alcohol drinking by bodyweight was highest during initial access, declined and then stabilized over the 16 sessions of voluntary access ( Figure 2 A, sessions 1–16). In support, the ANOVA for alcohol drinking (g/kg/24 h) with lesion (control vs. BLAx) and session (1–16) as factors, found a significant main effect of session ( F 15,330 = 6.43, p < 0.01).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous findings from our lab [ 5 , 7 ], alcohol drinking by bodyweight was highest during initial access, declined and then stabilized over the 16 sessions of voluntary access ( Figure 2 A, sessions 1–16). In support, the ANOVA for alcohol drinking (g/kg/24 h) with lesion (control vs. BLAx) and session (1–16) as factors, found a significant main effect of session ( F 15,330 = 6.43, p < 0.01).…”
Section: Resultssupporting
confidence: 91%
“…Adolescent alcohol drinking, particularly heavy drinking, is associated with increased risk for the development of alcohol use disorder in adulthood [ 2 , 3 ]. Consistent with observations in people, recent studies in rodents have shown that voluntary alcohol drinking in adolescence can increase alcohol drinking [ 4 ] or permit alcohol access to appetitive learning [ 5 ] in adulthood. While adolescents appear to be potentially more vulnerable to the effects of alcohol [ 6 ], the precise neural mechanisms that mediate this vulnerability have yet to be determined.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, differences in observed drinking patterns are not uncommon and can be due to a variety of methodological differences such as age, bottle type, housing conditions, and the nature of previous alcohol experience [ 25 , 44 ]. The pattern we observed is highly consistent with previous reports from our laboratory irrespective of [ 27 , 45 , 46 ] and following fear discrimination [ 47 ]. OF course, we cannot rule out that prior fear conditioning influenced alcohol consumption.…”
Section: Discussionsupporting
confidence: 93%
“…Heavy drinkers (n ¼ 8, Fig. 1B) were identified as rats whose mean alcohol drinking over the final four sessions was at least 10 g/kg per 24 h. This alcoholdrinking amount is comparable with the amount of drinking demonstrated by alcohol-preferring rat strains (Marchant et al 2013), is double terminal alcohol-drinking amounts observed in adult long evans rats (Simms et al 2008), and is similar to alcoholdrinking amounts necessary to observe positive alcohol reinforcement (DiLeo et al 2015). To control for access to alcohol, the eight rats showing the lowest alcohol drinking were identified as mod-erate drinkers (Fig.…”
mentioning
confidence: 68%